Service Quality and Customer Satisfaction in Last Mile Logistics: Evidence from a Courier and Parcel Delivery Firm - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Fundamental and Applied Management Journal, 2025)
This study investigates whether the SERVQUAL dimensions—tangibles, reliability, responsiveness, assurance, and empathy—predict customer satisfaction in a courier and parcel-delivery (last-mile logistics) company. A cross-sectional survey of 100 customers selected via purposive sampling was administered using multi-item Likert scales. Data were analyzed with multiple regression to estimate the marginal contribution of each dimension and to assess the joint (simultaneous) effect on satisfaction. The findings show that all five dimensions are positively and significantly associated with customer satisfaction, and the model confirms a significant joint influence. Responsiveness and empathy emerge as the strongest predictors, whereas assurance exhibits the weakest effect, indicating room for improvement in perceived security, reliability of commitments, and service guarantees. Managerially, the company should sustain strengths related to empathy, tangibles, and responsiveness (e.g., attentive staff, clear physical cues of service quality, swift handling of requests) while prioritizing initiatives that bolster assurance—such as transparent service policies, consistent delivery promises, and credibility signals. The study adds firm-level evidence from the last-mile logistics sector, reinforcing the relevance of SERVQUAL for explaining satisfaction in time-sensitive, technology-enabled delivery contexts.